Uptake and Utilization of S-Adenosyl-l-Methionine and S-Adenosyl-l-Homocysteine in an Adenine Mutant of Saccharomyces cerevisiae - Knudsen, Richard C. (1969)
An adenine mutant of Saccharomyces cerevisiae was able to utilize S-adenosyl-l-methionine (SAM), S-adenosyl-l-homocysteine (SAH), or adenine as sources for growth and ribonucleic acid (RNA) synthesis. Exogenous SAM or SAH was degraded after entering the cell, and the adenine moiety was reutilized in the endogenous synthesis of the thionium compounds. Part of this endogenous synthesis proceeds from an undetermined de novo system of purine synthesis which contributes significantly to the synthesis of SAM and less so to the RNA purines. Some of the methyl groups of exogenous SAM-methyl-(3)H were incorporated into ribosomal and transfer RNA. Methionine partially antagonized this incorporation. The uptake of SAM-adenine-8-(14)C was not affected by the presence of equal quantities of SAH or adenine in the medium. Exogenous SAM affected the uptake of exogenous SAH-adenine-8-(14)C or adenine-8-(14)C. Exogenous SAH inhibited the uptake of exogenous adenine-8-(14)C.